Dreams of the Rarebit Fiend: food and diet as instigators of bizarre and disturbing dreams - Nielsen, Tore; Powell, Russell A. (Frontiers in Psychology, 2015)
In the early 1900s, the Dream of the Rarebit Fiend comic strip conveyed how the spicy cheese dish Welsh rarebit leads to bizarre and disturbing dreams. Today, the perception that foods disturb dreaming persists. But apart from case studies, some exploratory surveys, and a few lab studies on how hunger affects dreaming, there is little empirical evidence addressing this topic. The present study examines 3 aspects of the food/dreaming relationship; it attempts to: 1) assess the prevalence of the perception of food-dependent dreaming and the types of foods most commonly blamed; 2) determine if perceived food-dependent dreaming is associated with dietary, sleep or motivational factors; and 3) explore whether these factors, independent of food/dreaming perceptions, are associated with reports of vivid and disturbing dreaming. 396 students completed questionnaires evaluating sleep, dreams, and dietary habits and motivations. Items queried whether they had noticed if foods produced bizarre or disturbing dreams and if eating late at night influenced their dreams. The perception of food-dependent dreaming had a prevalence of 17.8%; dairy products were the most frequently blamed food type (39%-44%). Those who perceived food-dependent dreaming differed from others by reporting more frequent and disturbing dreams, poorer sleep, higher coffee intake, and lower Intuitive Eating Scale scores. Reports of disturbing dreams were associated with a pathological constellation of measures that include poorer sleep, binge-eating, and eating for emotional reasons. Reports of vivid dreams were associated with measures indicative of wellness: better sleep, a healthier diet, and longer times between meals (fasting). Results clarify the relationship between food and dreaming and suggest 4 explanations for the perception of food-dependent dreaming: 1) food specific effects; 2) food-induced distress; 3) folklore influences, and 4) causal misattributions. Clinical implications are discussed.